Almost misdiagnosed Menkes disease: A case report. Issue 4 (April 2022) - Guo, Yu; Xia, Wei; Peng, Xuehua; Shao, Jianbo
Abstract: Background: Menkes disease is a disorder of copper metabolism and which follows a progressive degeneration of brain. It is a rare X-linked recessive disorder that results from mutations in ATP7A gene. The early diagnosis of Menkes disease is critical to patients' prognosis. Case presentation: We report a case of Menkes disease. A 4-month-old boy presented with intermittent convulsions for a week. The brain MRI showed excessive tortuosities of intracranial vessels, and radiologists prompted for further examinations to confirm that it was Menkes disease. Patient was advised for biochemical investigations and genetic tests. Reduced level of ceruloplasmin (0.04 g/L; normal range, 0.2–0.6 g/L) was revealed. Genetic testing revealed a missense mutation within exon 18, c.3548 G > A, p.G1183D. This patient was almost misdiagnosed as epilepsy. Fortunately, based on the clues from radiologist, further physical examination and experimental tests were carried out. Conclusion: We reported the imaging features of a case of Menkes disease, which can provide clinicians with more clues to consider the possibility of this rare disease. Abstract : Menkes disease; Pediatric; MRI; Rare disease; Case report.